Medidas tecnológicas para mitigar el cambio climático (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The present paper presents a worldwide overview of the energy sector, stressingthe focus in both, Europe and Spain. Firstly, sectors that contribute the most to climatechange with their CO2 emissions are highlighted. Additionally, it analizes awide variety of technological proposals related to the emission reduction challenge to 2020, that have been encouraged through directives or national plans. As a conclusion, it can be stated that all of these proposals are necessary for such an ambitious goal; more over, all initiatives relating to efficiency and energy saving appear to be particularly relevant. The promotion of research and development in pilot project sand technologies will significantly help to mitigate the climate change in the future.